The Effect of Team Games Tournament Model-Assisted Articulate Storyline Media on Improving Outcomes and Interest in Learning Javanese Script Material in Elementary School - Sekarsari, Elok Puspita; Rusnilawati, Rusnilawati (Mimbar Sekolah Dasar, 2023)
Javanese language is a national culture that needs to be protected and preserved to not lose its identity. In the Javanese script, education includes writing and reading skills starting from elementary school. This study was motivated by the difficulty of understanding Javanese script material in the classroom. This study aims to determine the Team Games Tournament learning (TGT) model using Articulate Storyline media to enhance student learning outcomes and interest in elementary school. The research method used is quantitative with a Quasi Experiment Design. The sampling technique used was purposive random sampling with two class samples for research, the experimental and control classes as a comparison. The sample consists of 50 fifth-grade students, with each class consisting of 25 students. The instruments used were test questions and interest questionnaires to measure the specified variables. Data analysis techniques in statistical testing are instrument, prerequisite, and hypothesis tests. The average post-test final result in the experimental class was 47.36, and the control class was 36.1. The results showed an influence on the TGT learning model with Articulate Storyline on improving learning outcomes and interest of elementary school students.